Doping mechanism of MoO3 in 4, 4′‐Bis(N‐carbazolyl)‐1, 1′‐biphenyl: A photoelectron spectroscopic study. Issue 9 (6th June 2016) - Kühn, Maybritt; Mankel, Eric; Köhn, Andreas; Mayer, Thomas; Jaegermann, Wolfram
Abstract : The doping mechanism of molybdenum oxide (MoO3 ) in the hole transport material 4, 4′‐Bis( N ‐carbazolyl)‐1, 1′‐biphenyl (CBP) is explored extensively using photoelectron spectroscopy. Doping limit and doping efficiency are investigated in dependence on the MoO3 content. In addition, shape changes in Mo3d and C1s core level spectra of doped layers are compared to the respective emissions of the pristine materials. Using density functional theory (DFT) calculations, the additional feature in the C1s emission can be assigned to CBP + cations and in the Mo3d emission a Mo5 + species can be identified. Therefore, charge transfer can not only be deduced indirectly from the movement of the Fermi level within the CBP energy gap, but also directly in the formation of cations of the matrix and anionic dopant species. Finally, the dopant morphology in dependence on the MoO3 content is derived indirectly from XPS measurements and is correlated to the observed doping efficiency. Because MoO3 precipitates form in the CBP matrix as evident from TEM measurements, the bilayer interface band alignment is analyzed by stepwise evaporation of CBP onto a MoO3 layer. The results of the interface experiment show that the CBP:MoO3 doping behavior can be well understood with the internal interface charge transfer doping model.